Two TOBAMOVIRUS MULTIPLICATION 2A homologs in tobacco control asymptomatic response to tobacco mosaic virus. Issue 4 (21st September 2021) - Hu, Qun; Zhang, Hui; Zhang, Lei; Liu, Yong; Huang, Changjun; Yuan, Cheng; Chen, Zefan; Li, Kunpeng; Larkin, Robert M; Chen, Jiongjiong; Kuang, Hanhui
Abstract: The most common response of a host to pathogens is arguably the asymptomatic response. However, the genetic and molecular mechanisms responsible for asymptomatic responses to pathogens are poorly understood. Here we report on the genetic cloning of two genes controlling the asymptomatic response to tobacco mosaic virus (TMV) in cultivated tobacco ( Nicotiana tabacum ). These two genes are homologous to tobamovirus multiplication 2A ( TOM2A ) from Arabidopsis, which was shown to be critical for the accumulation of TMV. Expression analysis indicates that the TOM2A genes might play fundamental roles in plant development or in responses to stresses. Consistent with this hypothesis, a null allele of the TOM2A ortholog in tomato ( Solanum lycopersicum ) led to the development of bent branches and a high tolerance to both TMV and tomato mosaic virus (ToMV). However, the TOM2A ortholog in Nicotiana glauca did not account for the asymptomatic response to TMV in N. glauca . We showed that TOM2A family is plant-specific and originated from Chlorophyte, and the biological functions of TOM2A orthologs to promote TMV accumulation are highly conserved in the plant kingdom—in both TMV host and nonhost species. In addition, we showed that the interaction between tobacco TOM1 and TOM2A orthologs in plant species is conserved, suggesting a conserved nature of TOM1–TOM2A module in promoting TMV multiplication in plants. The tradeoff between host development, the resistance of hosts to pathogens, and their influence on gene evolution are discussed. Our results shed light on mechanisms that contribute to asymptomatic responses to viruses in plants and provide approaches for developing TMV/ToMV-resistant crops. Abstract : Tobacco TOBAMOVIRUS MULTIPLICATION 2A homologs control the asymptomatic response to tobacco mosaic virus and have highly conserved biological functions related to virus multiplication.